The impact of digital technology affordances on radical innovation: moderating effects of industry technological turbulence and regional innovation environment - Xia, Liu; Yuan , Cheng; Yaqi, Wang (Transformations In Business & Economics, 2025)
To explore the mechanisms and conditions through which digital technology impacts radical innovation, this paper uses a sample of 409 firms to integrate digital technology affordances and radical innovation into the same research framework from the technology affordances’ perspective while also assuming the effect of industry technological turbulence and regional innovation environments. The impact of digital technology accumulation affordance, variation affordance, and their comprehensive balance on radical innovation shows an “inverted U-shaped” relationship. Industry technological turbulence and regional innovation environment have a negative moderating impact on the above relationships. From the interaction viewpoint between internal technology and the external environment, this study explains the conditions under which digital technology affects radical innovation, harnessing digital technology for radical innovation.
Keywords: accumulation and variation affordances; radical innovation; technological turbulence